2020
DOI: 10.1016/j.scitotenv.2020.140929
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal differentiation of COVID-19 epidemic spread in mainland China and its influencing factors

Abstract: Spatial and temporal differentiation of COVID-19 epidemic spread in China and its influencing factors are analyzed. • The global and local spatial correlation characteristics of the epidemic distribution present a positive correlation. • The population inflow from Wuhan and strength of economic connection are the main factors affecting the epidemic spread. • The interaction influence of detection factors on the epidemic spread exceeds that of the single factor. • When the average temperature in winter is maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 11 publications
8
99
2
4
Order By: Relevance
“…Our findings at the prefecture level on the impact of temperature conditions over the transmission of COVID-19 are not consistent with other published studies ( Prata et al, 2020 ; Wang, 2020 ). However, our results are consistent with several published studies ( He et al, 2020 ; Luo, 2020 ; Rashed et al, 2020 ; Xie et al, 2020 ), which reported that the changes in temperature in spring and summer months might not lead to decline of confirmed case counts without the implementation of extensive public health interventions.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings at the prefecture level on the impact of temperature conditions over the transmission of COVID-19 are not consistent with other published studies ( Prata et al, 2020 ; Wang, 2020 ). However, our results are consistent with several published studies ( He et al, 2020 ; Luo, 2020 ; Rashed et al, 2020 ; Xie et al, 2020 ), which reported that the changes in temperature in spring and summer months might not lead to decline of confirmed case counts without the implementation of extensive public health interventions.…”
Section: Discussionsupporting
confidence: 93%
“…As such, we analyzed the spatial evolution characteristics of epidemic sites by using NNI, kernel density, and SDE methods, providing a useful supplemental approach for studying the spatial distribution pattern of COVID-19. The analysis results show that the epidemic sites were spatially clustered; some studies have also found spatial clustering of COVID-19 at the national scale [ 14 , 16 , 25 ]. In Shenzhen, the epidemic sites have been mainly located in Futian District, Luohu District, and Nanshan District.…”
Section: Discussionmentioning
confidence: 90%
“…There are four stages that are required for zoonotic agents to emerge in humans: 1) human contact with the infectious agent; 2) cross-species transmission of the agent; 3) sustained human-to-human transmission and 4) genetic adaptation by the human host [3,4]. All these steps occurred when COVID-19 pandemic started in Wuhan, China on late December 2019 [5], and the possible initial source of the SARS-CoV-2 virus was a species of horseshoe bat found in caves in Yunnan Province [3,4,6,7]. It was also identified that secondary or intermediate hosts in which SARS-CoV-2 lived prior to reaching humans were likely the pangolins [8].…”
Section: Introductionmentioning
confidence: 99%